The Interconnection between Intellectual Achievement and Self-Control. (January 2013) - Boisvert, Danielle; Stadler, William; Vaske, Jamie; Wright, John P.; Nelson, Matthew
Low self-control has emerged as a strong predictor of criminal conduct and analogous behaviors. Questions remain, however, as to the origins of self-control. Whereas some argue it is a trait instilled solely through a process of parental socialization, more recent research has suggested the possibility that self-control is interconnected with many executive functions deriving from the prefrontal cortex of the brain. Using data from the Child Development Supplement of the Panel Study of Income Dynamics ( N = 2, 104), this study assesses the degree to which self-control is linked with intellectual achievement in childhood and adolescence. Results from Poisson regression analyses indicate that intellectual achievement is significantly related to variations in self-control, controlling for a variety of parenting measures; age, race, and gender; and previous levels of self-control. A discussion of the relationship between intellectual achievement and self-control is provided.